2018
DOI: 10.3906/sag-1712-160
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lenalidomide and dexamethasone in patients with relapsed/ refractory multiple myeloma: a real-life experience

Abstract: We found RD to be safe, well tolerated, and effective in RRMM in everyday clinical practice in Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…10 However, in the area of multiple myeloma-particularly in RRMM-, sociodemographic characteristics of study participants (aside from sex and age) are rarely reported, even in studies investigating these patients in the real-world setting. [15][16][17][18][19][20][21] Furthermore, most of these studies are focused on specific therapeutic agents, thus losing sight of the general profile of RRMM. Our analysis made it possible to provide an archetypal sociodemographic profile of RRMM patients in Spain, who are mostly men or women in their 60s or 70s, retired and living in an urban area with their relatives.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, in the area of multiple myeloma-particularly in RRMM-, sociodemographic characteristics of study participants (aside from sex and age) are rarely reported, even in studies investigating these patients in the real-world setting. [15][16][17][18][19][20][21] Furthermore, most of these studies are focused on specific therapeutic agents, thus losing sight of the general profile of RRMM. Our analysis made it possible to provide an archetypal sociodemographic profile of RRMM patients in Spain, who are mostly men or women in their 60s or 70s, retired and living in an urban area with their relatives.…”
Section: Discussionmentioning
confidence: 99%